1470‐nm Radial fiber‐assisted liposuction for body contouring and facial fat grafting - Heller, Lior; Menashe, Shaked; Plonski, Lori; Ofek, Andre; Pozner, Jason N. (Journal of cosmetic dermatology, 2022)
Background Laser‐assisted liposuction using 1470‐nm radial fiber emits light energy preferentially absorbed by water, yielding a rapid and localized contouring and tightening effect, with minimal scarring. When collected under appropriate conditions, extracted fat samples can be exploited as autologous filling material in liposculpturing procedures. Objectives To assess the 6‐month contouring efficacy of 1470 radial fiber‐assisted liposuction and the volumetric enhancement effect of the harvested tissue in facial fat grafting. Methods Twenty subjects underwent liposuction (BeautiFill, Alma Lasers, Inc.) of lower abdominal or outer thigh fat. In seven subjects, harvested samples were grafted into facial regions. Treatment safety, body weight, blinded evaluator‐assessed aesthetic improvements, and subject‐rated satisfaction were monitored for 6 months. Abdominal and facial fat thickness were assessed by magnetic resonance imaging (n = 5) within 3 months of treatment. Results One‐month posttreatment, most subjects ranked improvements good/excellent (88%) and skin tightening satisfactory/very satisfactory (92%), with >70% of subjects providing similar scores 6‐month posttreatment. Blinded evaluators noted improved/very much improved aesthetic appearance (87%). Harvested tissue injected as a facial filler (21.0 ± 5.2 ml) led to a 0.63 ± 0.12 mm increase in facial fat thickness, observed by MRI, within 3 months. Six months postfilling, the majority of subjects (83%) were satisfied with the outcome. All procedures were well‐tolerated. Conclusions A single 1470 nm radial fiber‐assisted abdominal and thigh liposuction session provided for effective and durable reduction of adipose tissue deposits, with appreciable skin tightening and aesthetic improvements. The gentle harvesting method yielded viable filler material, which was well‐retained in facial regions for up to 6 months.